THE UTILIZATION OF ZEOLITE AS MATERIAL PRODUCTION OF BIOPESTICIDE ACTIVE NEMATODA STEINERNEMA SPP. WITH GRANULAR SHAPED - Setyobudi, Bambang; Wagiyana, Wagiyana (Jurnal Zeolit Indonesia, 2008)
The study about biopesticide granular shaped has been conducted by utilizing zeolite and vertisol. Both materials are used as media that functions to storage Steinernema. The purpose of this study was to find method and formulas to produce biopesticide active nematodes with granular shaped that have high viability and effectiveness and can last long live. The result showed that drop method on combination of zeolite and vertisol material produce granule with Â± 8 mm diameter and weight of Â± 0.3 g. Biopesticide on granule shape that mixture result of zeolite, vertisol, and Steinernema spp. able to maintain viability of Steinernema spp. until nine weeks. The formulas to produce granule biopesticide an effective until nine weeks is a combinations of mixture 50% up to 75% zeolite on vertisol.